Jamblang (Syzygium Cumini (L.) Dan Bioaktivitasnya - Marina Silalahi (Interest : Jurnal Ilmu Kesehatan, 2018)
Backgoun: Syzygium cumini is a species in the Myrtaceae, which is used as traditional medicine. In Indonesia S. cumini found in the yard and home garden, which use as producer of fruit and shading. The using of natural product as traditional medicine is better than sintetic, but improper has a negative impact. This article aims to explain the uses of S. cumini as traditional medicine and its bioactivity. Method: This article is based on the study of literature obtained on line and off line such as used Web, Scopus, Pubmed, and scientific journals, then synthesized according to the research objectives so that comprehensive information. Result: The traditional medicine of S. cumini have been used to cure diabetes mellitus, anti-inflammation, anti-ulcers, vaginal discharge, stomach disorders, fever, stomach aches, wounds, digestive disorders, and skin infection. The bioassay of S. cumini has activities as anti-diabetes mellitus, antioxidant, antimicrobial, anti-allergy, anti-hyperlipidemic, anti-cancer, gastroprotective, hepatoprotective, cardioprotective, anti-inflammatory, and anti-pyretic. Conclusion. Our study of S. cumini is very potential to be developed as an anti-diabetes mellitus drug because it is considered safer therefore it is necessary to do further research.